Meaning and Grammar of Nouns and Verbs - Brenner, Dorothea; Czardybon, Adrian; Fleischhauer, Jens; Gamerschlag, Thomas; Gast, Volker; Gerland, Doris; Gerland, Doris; Geuder, Wilhelm; Herweg, Michael; Horn, Christian; Horn, Christian; Indefrey, Peter; et al. (düsseldorf university press, 2014)
The papers collected in this book cover contemporary and original research on semantic and grammatical issues of nouns and noun phrases, verbs and sentences, and aspects of the combination of nouns and verbs, in a great variety of languages. A special focus is put on noun types, tense and aspect semantics, granularity of verb meaning, and subcompositionality. The investigated languages and language groups include Austronesian, East Asian, Slavic, German, English, Hungarian and Lakhota. The collection provided in this book will be of interest to researchers and advanced students specialising in the fields of semantics, morphology, syntax, typology, and cognitive sciences
Keywords: cognition; conceptual noun types; definiteness; frame theory; morphology; noun semantics; perfectivity; syntax; telicity; typology; verb semantics; Nom (Linguistique); Parties du discours; Verbe (Linguistique); Grammar, Comparative and general; LANGUAGE ARTS & DISCIPLINES / General; Parts of speech; Grammar, Comparative and general -- Noun; Grammar, Comparative and general -- Verb; Grammatik; Substantiv; Semantik; Verb; Adrian Czardybon; Anita Mittwoch; black language; Byoong-Rae Ryu; case marker; Claire Moyse-Faurie; comparative lexicology; corpus-linguistic; Dieter Wunderlich; double nominative; Ekkehard König; frame account; frame; Gerhard Schurz; Grammar; Hana Filip; Hungarian; Japanese; Jens Fleischhauer; Korean; Lakhota; Laura Kallmeyer; Leon Stassen; Michael Herwig; noun class; noun-types; Nouns; objective conjugation; Peter Indefrey; phase quantification; phase-theoretical account; Pragmatic possession; Present Perfect Puzzle; psycho-linguistic; Ralf Naumann; referentiality; Robert D. van Valin; Sebastian Löbner; SFB 991; Tagalog; talicity; telic incremental theme predications; Teop; Thomas Gamerschlag; type shifts; Ulrike Mosel; Verbs; Volker Gast; white language; Wiebke Petersen; Wilhelm Geuder; Electronic books; Festschrift; Aufsatzsammlung